Analysis of mutation spectrum of common deafness-causing genes in Hakka newborns in southern China by semiconductor sequencing. Issue 38 (September 2018) - Zhao, Pingsen; Lin, Lifang; Lan, Liubing
Abstract : Abstract: Hearing loss is a common neurosensory disorder, approximately half of the cases are caused by genetic factors, and approximately 70% of hereditary hearing impairments are nonsyndromic hearing loss (NSHL). The mutations of GJB2 (gap junction beta-2 protein), GJB3 (gap junction beta-3 protein), SLC26A4 (solute carrier family 26 member 4), and MT-RNR1 (mitochondrially encoded 12S RNA) are the most common inherited causes of NSHL. Because of different genetic backgrounds, the mutation spectrum of these common deafness-causing genes varies among different regions in China. Because no data are known on these mutations among the Hakka population of Southern China, we aim to investigate the mutation spectrum to add these to neonatal screening and genetic counseling. A total of 1252 blood samples from newborns have been detected by semiconductor sequencing for 100 mutations loci of 18 deafness-causing genes. Of the participants, 95 subjects carried deafness-causing genes mutations with the carrier rate of 7.59%. The mutation frequencies of GJB2, SLC26A4, GJB3, and mitochondrial genes were 3.04%, 3.51%, 0.16%, and 0.88%, respectively. We followed up subjects with single-gene homozygous or compound heterozygous mutations. Our study firstly analyzed deafness-causing genes mutation spectrum in Hakka population, providing evidence for future neonatal screening and genetic counseling in this area.